Pendampingan Pembuatan Aksi Nyata Pada Platform Mardeka Belajar Untuk Guru Pendidikan Anak Usia Dini - Amanda, Rizki Surya; Hasni, Uswatul; Ismiatun, Asih Nur; Rosyadi, Akhmad Fikri; Siregar, Masyunita (Journal Of Human And Education (JAHE), 2024)
The impact of the implementation of real actions carried out by Early Childhood Education teachers has a positive influence on improving the quality of learning and teaching in schools. “Aksi Nyata” are concrete forms carried out by teachers to implement and develop various ideas and initiatives that have been learned through the Merdeka Mengajar Program. However, conditions in the field show that teachers still face several challenges and obstacles in making real actions so that the level of success is not yet comprehensive. The purpose of this service activity is to provide assistance in making Aksi Nyata on the Merdeka Mengajar platform for early childhood education teachers. This community service involved 30 teachers from formal and non-formal ECE institutions in Jambi City. The stages of assistance start from planning, implementation, evaluation and follow-up plans. The results of the assistance obtained data on improving teachers' abilities in compiling real actions, especially with the use of technology that makes it easier for teachers. The function of the learning community needs to be activated regularly so that teachers have the opportunity to share and learn together, especially in compiling real actions.